Photooxidation and Pentagalloyl Glucose Cross-Linking Improves the Performance of Decellularized Small-Diameter Vascular Xenograft In Vivo - Liu, Yuhong; Chen, Chunyang; Xie, Xinlong; Yuan, Haoyong; Tang, Zhenjie; Qian, Tao; Liu, Yalin; Song, Mingzhe; Liu, Sixi; Lu, Ting; Wu, Zhongshi (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract Small diameter vascular grafts have a significant need in peripheral vascular surgery and procedures of coronary artery bypass graft(CABG); however, autografts are not always available, synthetic grafts perform poorly, and allografts and xenografts , dilate, calcify and induce inflammation after implantation. We hypothesized that crosslinking of decellularized xenogeneic vascular grafts would improve the mechanical properties and biocompatibility, as well as reduce inflammation, degradation, and calcification in vivo. To test this hypothesis, bovine internal mammary artery (BIMA) was decellularized by detergents and ribozyme with sonication and perfusion. Photooxidation and penta-galloyl glucose (PGG)was used to crosslink the collagen and elastin fibers of decellularized xenograft. Modified graft’s characteristics and biocompatibility were studied in vitro and in vivo; the grafts were implanted as transposition grafts in the subcutaneous of rats and abdominal aorta of rabbits. The decellularized grafts were cross-linked by photooxidation and PGG, which improved the grafts’ biomechanical properties, biocompatibility, prevented elastic fibers from early degradation and reduced inflammation and calcification in vivo. Short-term aortic implants in the rabbits showed collagen regeneration and differentiation of host smooth muscle cells. No occlusion and stenosis occurred due to remodeling and stabilization of the neointima. Good patency rate(100%) was maintained. Notably, implantation of non-treated graft exhibited marked thrombosis, an inflammatory response, calcification, and elastin degeneration. Thus, photooxidation and PGG crosslinking are potential tools in the improvement of grafts’ biological performance within decellularized small diameter vascular xenograft.